PERAN KEBIJAKAN MONETER DAN FISKAL TERHADAP PERTUMBUHAN EKONOMI - Purwiyanti, Triska; Panjawa, Jihad Lukis (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa); Vol 7 No 2 (2022): Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa), 2022)
Economic instability has the potential to slow down the achievement of a country’s development and prosperity. An unstable economy can be seen from the decrease economic growth and will create vulnerability. This study aims to analyze the factors that influence economic growth in Indonesia. The determinants used include interest rates, exchange rate, tax ratio, and labor. The method used in this research is Ordinary Least Square (OLS) with multiple linear regression analysis tools. The results showed that interest rates has no significant on economic growth. While the ecxchange rates, tax redistribution, and labor have a positive significant on economics growth in Indonesia.